Inverse problem for the gravimetric modeling of the crust-mantle density contrast - TENZER, Robert (Contributions to Geophysics and Geodesy, 2013)
The gravimetric inverse problem for finding the Moho density contrast is formulated in this study. The solution requires that the crust density structure and the Moho depths are a priori known, for instance, from results of seismic studies. The relation between the isostatic gravity data (i.e., the complete-crust stripped isostatic gravity disturbances) and the Moho density contrast is defined by means of the Fredholm integral equation of the first kind. The closed analytical solution of the integral equation is given. Alternative expressions for solving the inverse problem of isostasy are defined in frequency domain. The isostatic gravity data are computed utilizing methods for a spherical harmonic analysis and synthesis of the gravity field. For this purpose, we define various spherical functions, which define the crust density structures and the Moho interface globally.